(untitled) (Revista de Ciências Agroveterinárias, 2005)
The ornamental plant production is mostly performed under protected cultive and using substrate as a growing way. The substrate is usually composed by several components to obtain the ideal physical and chemical characteristics to the plant development. These components, many times residues, should be offered in constant availability and quantity and localized next to the consumer center. The studied residue to the production of three ornamental spescies was the Vime’s bark (VB). It was mixed with comercial substrate (CS) to estimate the growth of Tagetes patula, Salvia splendens, Petunia grandiflora in different proportions of the mixture (100% VB; 75% VB+25%CS; 50%VB+50%CS; 25%VB+75%CS; 100%CS). The plant measured parameters were: height (cm), number of flowers, number of leaves, dry weight (g), number of branches and grade scale (1 to 5). The substrate estimated parameters were: salinity (g/L), pH, wet density (g/L), and dry density (g/L). Vime’s bark showed low salinity (0,84 g/L), and pH 6,4. All the Tagetes and Salvia’s estimated parameters did not show any diference at the 5% significance level, indicating that the vime’s bark quality was similar to the commercial substrate. The Petunia’s number of flowers, number of branches and dry weight were superior in the treatments with the presence of the vime’s bark when compared with the treatment with 100% of commercial substrate.